Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00701-006-0735-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidural cooling for selective brain hypothermia in porcine model

Abstract: The data demonstrate that epidural space cooling was technically feasible and useful for selective brain hypothermia, and the target temperatures are easily controlled. The induction of hypothermia was rapid and maintained for a long period of time, whereas the body temperature was maintained within the normal range and without hemodynamic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Accordingly, craniectomy with a larger area covering the ischemic region might be an option not only for decompression but also for a certain extent of regional hypothermia at the superficial cortex. 39 Furthermore, the documented temperature differences (26 C: À1.7 C and À0.7 C; 20 C: À3.5 C and À1.3 C; 14 C: À5.4 C and À1.9 C; 10 C: À6.3 C and À2.2 C at 3.16 mm and 6.40 mm distances, respectively) in the superficial cortex in our study suggested a lower cooling efficiency compared to direct liquid perfusion (20 C: À3ÀÀ4 C; 14 C: À9 C) 19,21 and cooling coil placed between the temporal muscle and skull (31 C: À5 C; 26 C: À10 C). 38 Our result clearly showed that the cooling effect was confined within a relatively small area, implying that multiple devices might be required in clinical applications.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Accordingly, craniectomy with a larger area covering the ischemic region might be an option not only for decompression but also for a certain extent of regional hypothermia at the superficial cortex. 39 Furthermore, the documented temperature differences (26 C: À1.7 C and À0.7 C; 20 C: À3.5 C and À1.3 C; 14 C: À5.4 C and À1.9 C; 10 C: À6.3 C and À2.2 C at 3.16 mm and 6.40 mm distances, respectively) in the superficial cortex in our study suggested a lower cooling efficiency compared to direct liquid perfusion (20 C: À3ÀÀ4 C; 14 C: À9 C) 19,21 and cooling coil placed between the temporal muscle and skull (31 C: À5 C; 26 C: À10 C). 38 Our result clearly showed that the cooling effect was confined within a relatively small area, implying that multiple devices might be required in clinical applications.…”
Section: Discussioncontrasting
confidence: 58%
“…For evaluating the cooling efficiency, the static brain temperature in our study was 32e33 C, lower than the 36 C of previous reports. 19,21,38 This could be due to the difference in surgical approach, as craniectomy was performed in our experimental setting for the placement of temperature probes and consequently promoted temperature radiation from the open skull. Accordingly, craniectomy with a larger area covering the ischemic region might be an option not only for decompression but also for a certain extent of regional hypothermia at the superficial cortex.…”
Section: Discussionmentioning
confidence: 98%
“…Several methods for inducing selective hypothermia within brain tissue have been proposed and implemented, which include epidural cooling, cooling helmet, nasopharyngeal cooling, forced convection using a fan, and cooling the blood supplied to the brain [1,3,6,10,18,19,22,34]. These experimental studies show positive neuroprotection of hypothermia in preventing permanent damage by decreasing the brain temperature by up to 7°C within an hour.…”
Section: Discussionmentioning
confidence: 97%
“…These experimental studies show positive neuroprotection of hypothermia in preventing permanent damage by decreasing the brain temperature by up to 7°C within an hour. However, the methods that result in the biggest temperature reductions within a short duration are the more invasive methods that may involve surgical intervention and patient discomfort, such as epidural cooling, direct cooling of the brain blood supply, and nasopharyngeal cooling [1,3,10,35]. In this study, the temperature of the brain during a proposed non-invasive spinal cord hypothermia treatment session is simulated.…”
Section: Discussionmentioning
confidence: 98%
“…Epidural cooling -Cheng et al 41 used continuous epidural irrigation with chilled saline administered via burr holes to convectively cool the brain. In their porcine model, they achieved epidural temperatures of 13°C, subdural temperatures of 19°C and parenchymal temperatures of 28°C.…”
Section: Compartmental Coolingmentioning
confidence: 99%